A history of Saudi Arabia - Al-Rasheed, Madawi (New York : Cambridge University Press, 2010)
"This updated edition analyses the challenges, both internal and external, facing Saudi Arabia in the twenty-first century. Two new chapters discuss the political, economic and social developments in the aftermath of 9/11, painting a vivid picture of a country shocked by terrorism and condemned by the international community. Madawi Al-Rasheed reveals that fragmentation of royal politics, a failing economy and fermenting Islamist dissent posed serious threats to state and society in 2001. She assesses the consequent state reforms introduced under pressure of terrorism, international scrutiny and a social mobilisation of men, women and minorities struggling to shape their future against a background of repression and authoritarian rule. While Saudi Arabia is still far from establishing a fourth state, there are signs that the people are ready for a serious change that will lead them to a state of institutions rather than princes"--Provided by publisher.
Machine generated contents note: Introduction; 1. Society and politics, 1744-1818 and 1824-1891; 2. The emerging state, 1902-1932; 3. Control and loyalty, 1932-1953; 4. The politics of dissent, 1953-1973; 5. From affluence to austerity, 1973-1990; 6. The Gulf War and its aftermath, 1990-2000; 7. Narratives of the state, narratives of the people; 8. The challenges of a new era; 9. Modernising authoritarian rule.
Includes bibliographical references (p. 291-305) and index.
Keywords: History & geography -- Islamic History; Saudi Arabia -- History -- 21st century